COVID-19 in Nursing Facilities: Experience in Republic of Korea - Song, Rok (Osong Public Health Res Perspect, 2020)
OBJECTIVES: Coronavirus disease 2019 (COVID-19) outbreaks in nursing facilities can easily lead to a high rate of infection and fatality. A surge in newly infected cases in the first quarter of 2020 in Gyeongsan-si, in the Republic of Korea, was followed by several outbreaks in nursing facilities in the same area. The aim of this study is to report on the epidemiological investigation and the management to reduce the infection rate in nursing facilities for older adults. METHODS: The municipal government and the Korea Centers for Disease Control and Prevention performed an epidemiological investigation into 5 nursing facilities that reported a high number of COVID-19 infection cases from February to May 2020. COVID-19 infected cases in the facilities were investigated to identify the infection routes, and the fatality rate of the 5 facilities. RESULTS: The 5 facilities had a combined fatality rate of 12.2% (9 deceased among the 74 infected cases). The median age of the deceased was 87 years old (range: 82–91). The infection was first identified on February 27(th), 2020, peaked on March 6(th), and was last detected on March 24(th), 2020. CONCLUSION: Difficulties specific to such facilities included the delay in the recognition of symptoms and limitation in distancing. Tailored strategies such as daily monitoring of symptoms and proactive COVID-19 screening of quarantined residents, contributed to a decline in the infections in the facilities.